KESENIAN MANORTOR PADA TRADISI MANJONGJONG ADATDI NAGARI PEMATANG PANJANG KECAMATAN KOTO BALINGKAKABUPATEN PASAMAN BARAT - Halida, Neni; Hakim, Uswatul (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to identify the differences in the implementation of the Manjongjong Adat tradition between the descendants of kings and ordinary people, examine the requirements for performing Manortor art in this tradition during wedding ceremonies, and understand the functions contained in Manortor art as part of the Mandailing customary tradition. This research is qualitative with a descriptive analytical method. The research instrument is the researcher themselves, supported by writing tools and a camera. Data collection techniques include literature review, observation, interviews, and documentation. The steps for data analysis are data collection, data reduction, data presentation, and drawing conclusions. Research results indicate that the Manortor Art in the Manjonong Custom Tradition in Nagari Pamatang Panjang, Koto Balingka District, West Pasaman Regency is the Manortor Tradition in the Manjongjong Custom procession at Mandailing community weddings in Jorong Aek Nabirong, which is a cultural heritage rich in spiritual, social, and symbolic values within a preserved customary structure. Manortor is not merely a traditional dance, but a cultural communication medium to honour ancestors, affirm social structure, and implement customary law. The Manjongjong Tradition marks the official enforcement of customs, distinguishing the status of royal descendants and ordinary people through symbols such as the raising of customary flags and the presentation of a goat. The Manortor procession is carried out in stages, reflecting social hierarchy: starting from Tortor Raja, Tortor Suhut, Tortor Naposo Nauli Bulung, to Tortor Pengantin. The main functions of Manortor include: (1) ritual function as a form of spiritual respect, (2). The Manortor procession is carried out gradually, reflecting the social hierarchy: starting from Tortor Raja, Tortor Suhut, Tortor Naposo Nauli Bulung, to Tortor Pengantin. The main functions of Manortor include: (1) a ritual function as a form of spiritual respect, (2) an entertainment function that strengthens social bonds, and (3) a spectacle function as a medium for education and the preservation of Mandailing cultural identity. Thus, Manortor not only reinforces traditional values but also maintains cultural continuity amidst the tide of modernisation.